2021
DOI: 10.1098/rspa.2020.0853
|View full text |Cite
|
Sign up to set email alerts
|

A focusing and defocusing semi-discrete complex short-pulse equation and its various soliton solutions

Abstract: In this paper, we are concerned with a semi-discrete complex short-pulse (sdCSP) equation of both focusing and defocusing types, which can be viewed as an analogue to the Ablowitz–Ladik lattice in the ultra-short-pulse regime. By using a generalized Darboux transformation method, various soliton solutions to this newly integrable semi-discrete equation are studied with both zero and non-zero boundary conditions. To be specific, for the focusing sdCSP equation, the multi-bright solution (zero boundary condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…This induces an additional symmetry on the Lax operators 𝑋 * (𝑥, 𝑡, −𝑘 * ) = 𝑋(𝑥, 𝑡, 𝑘), 𝑇 * (𝑥, 𝑡, −𝑘 * ) = 𝑇(𝑥, 𝑡, 𝑘), (38) and assuming uniqueness of solution of the equations of the Lax pair with prescribed boundary conditions as 𝑥 → ±∞, then the last symmetry implies…”
Section: Real Solutions Of the Ccspementioning
confidence: 99%
See 1 more Smart Citation
“…This induces an additional symmetry on the Lax operators 𝑋 * (𝑥, 𝑡, −𝑘 * ) = 𝑋(𝑥, 𝑡, 𝑘), 𝑇 * (𝑥, 𝑡, −𝑘 * ) = 𝑇(𝑥, 𝑡, 𝑘), (38) and assuming uniqueness of solution of the equations of the Lax pair with prescribed boundary conditions as 𝑥 → ±∞, then the last symmetry implies…”
Section: Real Solutions Of the Ccspementioning
confidence: 99%
“…[1,[33][34][35][36][37], and dark soliton solutions of the defocusing cSPE have been obtained in Refs. [38,39]. The inverse scattering transform (IST) to solve the initial-value problem for the focusing cSPE equation was developed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, when we take the large-period limits, both of them degenerate to the Peregrine soliton [26], which is localized both in time and space and turns into a prototype of RWs. It turns out that this idea has been widely adopted in constructing RW solutions of many other integrable equations and their multi-component generalizations [15,27].…”
Section: The Nonlinear Schrödinger Equation (Nlse)mentioning
confidence: 99%
“…It is well-known that MI is one of the most ubiquitous phenomena in nature and commonly appears in many physical contexts such as water waves, plasma waves and electromagnetic transmission lines [13]. Whereas recent theoretical developments indicated that the presence of baseband MI supports the generation of rogue waves (RW) [14], breathers also appear to be a significant strategy in deriving RW solutions of many integrable equations [16,15].…”
Section: Introductionmentioning
confidence: 99%
“…Following the integrable discretization work of the two pioneers Ablowitz and Hirota [6,7], there are an abundant discrete soliton equations that are proposed and studied by some well-established methods [8][9][10][11]. Therefore, a series of exact solutions including the discrete soliton solution, breather, positon solution and the rogue wave solutions are investigated [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%